Cuidados de pie diabético en pacientes con diabetes mellitus tipo 2 que acuden al Hospital Isidro Ayora Loja. - Ortega Ortega, Karen Alejandra (2016)
This research descriptive, cross-called "care of diabetic foot in patients with type 2 Diabetes who attend public hospitals in the city of Loja." Due to compliance with the prerequisite to obtaining the title of Doctor General National University of Loja.The main objective to achieve with this study is to diabetic foot care in patients with type 2 Diabetes mellitus, as it incentivize the implementation of practices that improve their health and that knowledge and education are essential to prevent complications. For reliable and meaningful data we used the interview a research tool, applied to / as diabetic patients attending the outpatient service and hospitalization. The information collected reflects that 78% of the surveyed population has no knowledge about foot care, 21% know how to care, a percentage of the population does not use healthy practices in their daily lives to care for your feet; do not select proper footwear, which is referred by the economic limitation but not by ignorance, just as they do not know what the correct washing and drying your feet and use creams or lotions or moisturizers in them; also they not cut your nails properly, which favors the appearance of ingrown toenails, cracks, leading to possible infections which even in the future could lead to future amputations